2018
DOI: 10.1128/iai.00889-17
|View full text |Cite
|
Sign up to set email alerts
|

Diaphorina citri Nymphs Are Resistant to Morphological Changes Induced by “Candidatus Liberibacter asiaticus” in Midgut Epithelial Cells

Abstract: "Candidatus Liberibacter asiaticus" is the causative bacterium associated with 24 citrus greening disease. "Ca. L. asiaticus" is transmitted by Diaphorina citri more efficiently 25 when it is acquired by nymphs rather than adults. Why this occurs is not known. We compared 26 midguts of D. citri reared on healthy or "Ca. L. asiaticus"-infected citrus trees using quantitative 27 PCR, confocal microscopy, and mitochondrial superoxide staining for evidence of oxidative 28 stress. Consistent with its classification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
75
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(80 citation statements)
references
References 41 publications
(61 reference statements)
4
75
1
Order By: Relevance
“…In our study, the near systemic invasion of CLas in most of the ACP organs and tissues examined, including the epidermis of a leg ( Figure 7A), supported previous FISH and qPCR studies indicating a wide distribution of CLas in infected ACP [5,6,10,22,29], as well as ultrastructural, qPCR and FISH studies that have indicated an almost systemic invasion of the zebra chip pathogen CLso in the potato psyllid vector [11,27,30]. The near systemic distribution of both Liberibacter pathogens in their psyllid vectors was similar to that of other circulative-propagative hemipteran born bacterial phytopathogens, viz.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In our study, the near systemic invasion of CLas in most of the ACP organs and tissues examined, including the epidermis of a leg ( Figure 7A), supported previous FISH and qPCR studies indicating a wide distribution of CLas in infected ACP [5,6,10,22,29], as well as ultrastructural, qPCR and FISH studies that have indicated an almost systemic invasion of the zebra chip pathogen CLso in the potato psyllid vector [11,27,30]. The near systemic distribution of both Liberibacter pathogens in their psyllid vectors was similar to that of other circulative-propagative hemipteran born bacterial phytopathogens, viz.…”
Section: Discussionsupporting
confidence: 90%
“…However, no immunolabeling or molecular labeling methods were available to confirm the identity of such bacteria in these studies. Later, using fluorescent in situ hybridization (FISH) or qPCR indicated the presence of CLas in most organs and tissues of CLas-infected D. citri adults from Florida [6,7,10,22]. More recently, Ghanim et al [16] used FISH and immunogold labeling to describe CLas accumulation in the cells of ACP midgut.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3D-G and 5A-E), in agreement with our previous findings 27 . Electron and immunofluorescence microscopy analyses have revealed similar findings in spiroplasmas [6][7][8] and liberibacter 40,41 . Thus, the visceral muscles of the alimentary canal appear to be a common infection site for insect-borne plant pathogenic bacteria that are transmitted in a persistent propagative manner.…”
Section: Discussionmentioning
confidence: 54%
“…Given that Las is known to affect expression of CYP4 genes, this may also be the result of co-evolution. Indicating that one population is more tolerant of Las infection than the other (Ammar et al, 2016; Arp et al, 2016; Mann et al, 2018). The exact effect of these changes and why this movement would not affect Louisiana populations is unknown.…”
Section: Discussionmentioning
confidence: 99%